Formalismo de Input-Output aplicado em cavidades ópticas e geração de fótons individuais - Santos, Lucas Ribeiro da Silva (Universidade Federal de São Carlos, 2024)
This monograph will present the investigation of a possible emitter of the single photon state. This type of source is currently essential for information processing, especially for the development of quantum sensing, quantum communication and quantum computing. Consequently, a study is developed on an open quantum system in the context of Quantum Cavity Electrodynamics, through the Jaynes-Cummings (J-C) radiation-matter interaction model. Using a quantum optics tool, the Input-Output formalism, we investigate the properties of the output field of an optical cavity. A continuous coherent input field or a Gaussian pulse is considered, where both interact with the trapped atom, according to the J-C model. In different scenarios, the projection of the cavity exit field into a state containing exactly 1 photon is consistently observed. We analyze our system in realistic situations, such as taking into account losses in the atom. We then investigated how the parameters of our system, such as the shape of the pulse (intensity and duration) and the intensity of the atom-field coupling, influence the production of single photons and how it is possible to improve the probability of generating such states.
Input-Output formalism applied in optical cavities and single photon generation
Keywords: Formalismo Input-Output; Input-Output formalism; Jaynes-Cummings; Fótons individuais; Single photons; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR